Risk factors and predictive thresholds for postoperative pleural effusion in children with neuroblastoma: a retrospective cohort study - Jing Hu; Ping Chu; Jun Feng; Xinran He; Lijing Li; Yi Ren; Zhe Su; Wei Yang; Jianmin Zhang; Fang Wang (World Journal of Surgical Oncology)
Abstract Background Postoperative pleural effusion is a common complication after neuroblastoma resection in children. Evidence-based risk stratification remains limited. This study aimed to identify independent risk factors for postoperative pleural effusion and to establish clinically actionable thresholds for perioperative risk mitigation. Methods We analyzed 165 pediatric patients who underwent abdominal neuroblastoma resection between 2018 and 2020. Data regarding 82 variables across five dimensions were retrospectively collected from the preoperative period to 3 years postoperatively. The primary endpoint was postoperative pleural effusion requiring intervention. Continuous variables were dichotomized using cutoff values derived from receiver operating characteristic (ROC) curves to maximize outcome discrimination. Multivariable logistic regression was utilized to identify independent risk factors for postoperative pleural effusion; adjusted odds ratios (aORs) reflected the magnitude of association. Results Postoperative pleural effusion requiring intervention occurred in 21.82% of neuroblastoma patients. ROC curve analysis identified critical thresholds for risk factors: body mass index (BMI) Z-score = -0.96 SD, preoperative hemoglobin = 99.00 g/L, operative time = 4.33 h, albumin on postoperative day 1 = 32.30 g/L, and C-reactive protein on postoperative day 1 = 20.00 mg/L. Multivariable logistic regression analysis revealed that a slightly below-normal BMI Z-score (aOR = 10.20; 95% confidence interval [CI], 1.11–92.20; P = 0.039), adrenal origin of the tumor (aOR = 16.20; 95% CI, 1.21–215.60; P = 0.035), lower preoperative hemoglobin (aOR = 9.88; 95% CI, 1.69–57.76; P = 0.011), prolonged operative time (aOR = 180.20; 95% CI, 7.43–4373.99; P = 0.001), lower albumin on postoperative day 1 (aOR = 17.13; 95% CI, 3.26–90.14; P < 0.001), and elevated C-reactive protein on postoperative day 1 (aOR = 6.07; 95% CI, 1.21–30.40; P = 0.028) were independently associated with an increased risk of postoperative pleural effusion. Conclusions In pediatric patients undergoing neuroblastoma resection, prolonged operative time may indicate increased systemic inflammation. Perioperative inflammation modulation might represent a potential target for risk reduction, while maintaining adequate albumin levels and optimizing preoperative nutrition could be considered as supportive strategies. These findings are preliminary and require confirmation in larger prospective studies. Trial registration Chinese Clinical Trial Registry (ChiCTR2500096561; 01/26/2025).